Optimal renewal of definite integrals of monotone functions from the class H^ω - Busarova, T. N. (Ukrains’kyi Matematychnyi Zhurnal, 1997)
We obtain an exact estimate of the error of optimal renewal of an integral on a set of functions f(t) monotone on [a, b] with a convex majorant of the modulus of continuity, provided that |f(b) − f(a)| = L > 0.